Safety and Efficacy of a Well-Fitting Brassiere after Breast Reconstruction: A Qualitative Study - Watanabe, Satoko; Saiga, Miho; Motoki, Takayuki; Shien, Tadahiko; Taira, Naruto; Doihara, Hiroyoshi; Kimata, Yoshihiro (Acta medica Okayama, 2023)
The importance of a well-fitted, comfortable brassiere to overall quality of life after breast reconstruction has not been evaluated. Our aim was to determine the impact of a semi-customized brassiere on patients' health-related quality of life after breast reconstruction. The subjects were prospective patients with mastectomy who were to undergo immediate or delayed breast reconstruction at our hospital. After surgery, a professional bra fitter sized each patient for a semi-customized brassiere and provided follow-up consultations. A self-reported questionnaire on breast aesthetics, postoperative pain, and satisfaction was used to assess the primary outcomes. Data were prospectively collected at baseline (before surgery) and at 1, 3, 6, and 12 months after surgery and analyzed. Forty-six patients (50 breasts) were included in the analysis. Consistent wearing of the brassiere reduced pain (p<0.05), with good overall satisfaction (p<0.001). Aesthetic scores on breast shape and size were higher with than without the custom brassiere at 3 months (p=0.02) and 6 months (p=0.03) after surgery. Wearing the brassiere reduced anxiety at all time points of measurement. A well-fitting brassiere ensured safety and provided a high degree of satisfaction without anxiety for patients after breast reconstruction.